2021
DOI: 10.3390/polym13234225
|View full text |Cite
|
Sign up to set email alerts
|

Mastoparan, a Peptide Toxin from Wasp Venom Conjugated Fluvastatin Nanocomplex for Suppression of Lung Cancer Cell Growth

Abstract: Lung cancer has a very low survival rate, and non-small cell lung cancer comprises around 85% of all types of lung cancers. Fluvastatin (FLV) has demonstrated the apoptosis and suppression of tumor-cell proliferation against lung cancer cells in vitro. Drug–peptide nanoconjugates were found to enhance the cytotoxicity of anti-cancer drugs. Thus, the present study aimed to develop a nanocomplex of FLV with mastoparan (MAS), which is a peptide that has membranolytic anti-tumor activity. The nanocomplex of FLV an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…When comparing these data with the literature, it can be observed that the response of Jurkat cells to the crude venom of Polybia paulista wasp differs from that found for Brazilian Journal of Development, Curitiba, v.10, n.1, p. 696-707, jan., 2024 concentrations of 5 µg and 10 µg of crude venom from Apis mellifera on HL-60 cells, which resulted in an increase in cells in the S phase and a decrease in cells in the G1 phase (Lee et al, 2007). Conversely, a study on cell cycle analysis conducted by Alhakamy et al (2021) showed that synthetic mastoparan was able to increase the number of cells in the G0/G1 and G2/M phases in an alveolar adenocarcinoma cell line (A549), demonstrating the ability of this peptide to cause cell cycle arrest.…”
Section: Resultsmentioning
confidence: 99%
“…When comparing these data with the literature, it can be observed that the response of Jurkat cells to the crude venom of Polybia paulista wasp differs from that found for Brazilian Journal of Development, Curitiba, v.10, n.1, p. 696-707, jan., 2024 concentrations of 5 µg and 10 µg of crude venom from Apis mellifera on HL-60 cells, which resulted in an increase in cells in the S phase and a decrease in cells in the G1 phase (Lee et al, 2007). Conversely, a study on cell cycle analysis conducted by Alhakamy et al (2021) showed that synthetic mastoparan was able to increase the number of cells in the G0/G1 and G2/M phases in an alveolar adenocarcinoma cell line (A549), demonstrating the ability of this peptide to cause cell cycle arrest.…”
Section: Resultsmentioning
confidence: 99%
“…At present, the AVP database (http://crdd.osdd.net/servers/avpdb) (accessed on 29 December 2023) contains 2683 targeted AVPs related to more than 60 antiviral medicines that have great potential to become antiviral drugs [6]. Mastoparan family peptides derived from wasp venom exert various pharmacological effects, including bacteriostasis, immune regulation, and antitumor effects [16][17][18]. However, the antiviral function of natural wasp venom peptides has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Wasp venom contains a variety of bioactive substances, among which Mastoparan family peptides are a class of small-molecule peptides with the highest content and the largest number of members in wasp venom [ 15 , 16 ]. Previous studies have shown that Mastoparan family peptides are an important class of lead drug peptide molecules that have various pharmacological effects, such as inhibiting bacterial infection, regulating the immune system, and providing antitumor activity [ 16 , 17 , 18 ]. However, the antiviral functions of natural wasp venom Mastoparan family peptides are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…or subcutaneously (s.c.); Table ). M7-NH2 is a mucosal adjuvant and mast-cell-activating oligopeptide (Ile-Asn-Leu-Lys-Ala-Leu-Ala-Ala-Leu-Ala-Lys-Ala-Leu-Leu-NH2) which originated from the mastoparan peptide toxin found in wasp venom. …”
Section: Anti-cocaine Vaccinesmentioning
confidence: 99%